Hyper-Coordinated DNA Methylation is Altered in Schizophrenia and Associated with Brain Function. Issue 1 (31st July 2021) - Chen, Junfang; Schwarz, Kristina; Zang, Zhenxiang; Braun, Urs; Harneit, Anais; Kremer, Thomas; Ma, Ren; Schweiger, Janina; Moessnang, Carolin; Geiger, Lena; Cao, Han; Degenhardt, Franziska; et al.
Abstract: DNA methylation is an epigenetic biological process that is emerging as an important mediator of environmental risk effects on the susceptibility of severe illness, such as schizophrenia. DNA methylation shows coordination across biologically-related genes, but it is not known whether the resulting network structure has a mediating effect on illness risk. Here we identified a large gene network with hyper-coordinated DNA methylation in several biological processes that are changed in the brain of patients with schizophrenia, and that are associated with schizophrenia-relevant brain function as well as genetic illness susceptibility. We found that DNA methylation was physiologically coordinated in a reproducible network that comprised 6399 genes and showed a similar architecture in blood and brain. The network was hyper-coordinated in biological processes of core importance for schizophrenia, including synaptic processes that are associated with the strongest common genetic risk variants for schizophrenia. Coordinated methylation in these processes was decreased in brain samples from donors with schizophrenia, and showed an age-dependent association with schizophrenia-relevant brain function. These results support the coordination of DNA methylation as a regulatory principle relevant to schizophrenia that may be sensitive to environmental risk exposure during specific developmental periods and compound genetic illness predisposition.